Peran Akuntansi Forensik Dalam Pemberantasan Tindak Pidana Korupsi - Muhammad Jarnawansyah (Lembaga Pengembangan Kinerja Dosen, 2023)
Corruption is a serious problem that affects many countries around the world. Corruption hurts the economy, undermines the justice system, and hinders social development. Therefore, serious efforts are needed to fight corruption. One of the effective tools in eradicating corruption is forensic accounting. Forensic accounting involves the application of accounting principles and investigative analysis to uncover acts of corruption. This paper aims to explore the role of forensic accounting in eradicating corruption, including the methods used, their use in corruption investigations, and their benefits in the judicial process.